Analisis Interaksi Sosial Antara Tenaga Kesehatan Dan Pasien Dalam Pelayanan Kesehatan - Ahmad Hilal; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Abstract This study aims to analyze social interaction between healthcare workers and patients in healthcare services. Social interaction plays a crucial role in determining service quality and patient satisfaction. This research uses a qualitative descriptive approach, with data collected through in-depth interviews, observations, and documentation. The results show that effective communication, empathy, and professional attitudes of healthcare workers significantly influence patient trust and comfort. Social interaction occurs in both verbal and nonverbal forms, where clear explanations and supportive body language enhance patient understanding. However, several barriers were identified, including limited consultation time, high workload, and differences in social and cultural backgrounds. Furthermore, the findings indicate a significant relationship between the quality of social interaction and patient satisfaction, as supported by a Chi-Square analysis. Good interaction improves patient compliance, reduces anxiety, and enhances overall healthcare outcomes. Therefore, improving interpersonal communication skills among healthcare workers is essential to achieve better healthcare service quality. Keywords: Communication, Social Interaction, Patient Satisfaction, Healthcare Workers Abstrak Interaksi sosial dalam pelayanan kesehatan memiliki peran strategis dalam membangun hubungan antara tenaga kesehatan dan pasien. Penelitian ini bertujuan untuk mengkaji bentuk, faktor, serta dampak interaksi sosial dalam pelayanan kesehatan. Pendekatan yang digunakan adalah kualitatif deskriptif dengan pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa interaksi yang baik ditandai dengan adanya komunikasi dua arah, empati, serta penghargaan terhadap pasien. Sebaliknya, interaksi yang kurang optimal dipengaruhi oleh beban kerja tinggi dan kurangnya pelatihan komunikasi. Dampak dari interaksi yang baik adalah meningkatnya kepuasan dan kepatuhan pasien terhadap pengobatan. Oleh karena itu, diperlukan upaya peningkatan kualitas komunikasi dalam pelayanan kesehatan. Kata Kunci: Komunikasi Kesehatan, Interaksi Sosial, Kepuasan Pasien, Tenaga Medis